BREAKDOWN MAINTENANCE AND ROUTINE CARE OF THE BELT BUCKET ELEVATOR AT PT XYZ - Achmad Abiel Fauzi; Miftahul Jannah (Department of Mechanical Engineering, Universitas Sultan Ageng Tirtayasa, 2026)
Within animal feed manufacturing, the belt bucket elevator stands out as a vital bulk-handling unit, tasked with lifting raw materials vertically from the conveyor to the mixing tank ahead of the pelleting stage. At PT XYZ the machine runs around the clock across three shifts (24 hours per day), an operating pattern that leaves its components highly sontoto exposed to accelerated wear. Field observations gathered during a two-month internship surfaced two damage patterns that kept recurring: the rubber belt turning brittle and cracking, and progressive thinning of the bucket lip driven by repeated abrasive contact with feed materials such as corn, soybean meal, and camelina-flower meal. Component service lives logged in the field hovered at only one to two years — far short of the manufacturer’s design figures of three to four years for the belt and two to three years for the bucket and the mounting bolts. This work investigates the root causes behind such premature failure, audits the preventive maintenance practice codified in internal SOP WI-03/MTN/C01, and frames a set of targeted improvements.